A Comparison of Clinical, Electro-Diagnostic, Laboratory, and Treatment Outcome Differences in a Cohort of HIV-Infected and HIV-Uninfected Patients With Myasthenia Gravis - Moodley, Kaminie; Bill, Pierre L. A.; Patel, Vinod B. (Frontiers in Neurology, 2021)
Abstract: There is limited literature comparing the clinical parameters and treatment outcomes in HIV-infected and HIV-uninfected Myasthenia Gravis (MG) patients. The aim of the study was to investigate the clinical differences and treatment outcomes in the 2 categories of patients, especially the safe use of immunosuppressive therapy in immunocompromised patients. The study was a retrospective analysis of medical records of MG patients from the neuromuscular unit at Inkosi Albert Luthuli Central Hospital in Kwa-Zulu Natal between 2003 and 2019. One hundred and seventy eight (178) patients fulfilled the clinical criteria for MG. Twenty four (13.4%) were HIV-infected and 154 (86.5%) were HIV-uninfected. There were 116 (65%) females, median 45 years, (IQR 40-62), 90 (50.5%) black African, 66 (37%) Indian, 20 (11.2%) white and 2 (1.1%) of mixed ancestry. In the HIV-infected cohort, 20 (87%) had generalised MG, 12 (50%) bulbar and 14 (60.9%) respiratory onset MG, 12 (50%) presented with MG Foundation of America (MGFA) class 5 disease at diagnosis, 6 (25%) presented with MG crisis during the 5 year follow up. Thirteen (54%) of the HIV-infected group required rescue therapy using (plasma exchange or IV immunoglobulin) combined with pulse cyclophosphamide compared to 17 (11%) in the HIV-uninfected cohort respectively. At 5 years, 8 (33%) of the HIV-infected group remained refractory to treatment compared to 10 (6.5%) HIV-uninfected cohort respectively. No adverse events were documented in HIV-infected patients receiving combination rescue therapy (PLEX or IVIG combined with IV cyclophosphamide). In conclusion HIV-infected MG patients are more likely to require combination rescue therapy with PE/IVIG and IV cyclophosphamide compared to those who were HIV-uninfected. No side effects were documented in the HIV-infected group receiving the above therapy.